Acute effects of different dietary polysaccharides added in milk on food intake, postprandial appetite and glycemic responses in healthy young females. (17th August 2016) - Arshad, Muhammad Umair; Ishtiaq, Saima; Anjum, Faqir Muhammad; Saeed, Farhan; Chatha, Shahzad Ali Shahid; Imran, Ali
Abstract: In the present study we compared the postprandial glycemic and satiety responses of different dietary polysaccharides when added in milk (2% M.F.). The objective of this study was to evaluate different polysaccharides against postprandial glucose, appetite responses and food intake at subsequent meal. In a repeated measures design, 30 females (18–30 years) consumed 250 ml milk 2% M.F. (control), or milk with carrageenan (2.5 g), guar gum (2.5 g) and alginate (2.5 g), followed by an ad libitum pizza meal after 120 min. Alginate and guar gum addition resulted in lower caloric intake at subsequent pizza meal. The post-treatment (0–120 min) glucose and average appetite were suppressed by alginate and guar gum ( p  < 0.0001), with more pronounced effect of guar gum. However, alginate resulted in lower blood glucose ( p  < 0.0001) compared with control and carrageenan during post-treatment. Alginate and guar gum added beverages would be beneficial in short-term regulation of postprandial glycemia and satiety.